Polymer electrolytes for lithium secondary batteries - Gray, Fiona M. (2016)
The lithium-ion polymer battery concept provides a battery which is light and flexible, can undergo denser packaging than its liquid electrolyte counterpart, and need not be restricted in its final shape, size and geometry. Lithium-ion polymer cells which first appeared in consumer electronics in the mid-1990s are polymer gel electrolytes, a compromise between liquid electrolyte and completely solvent-free systems. The technology for these devices evolved from the already-established liquid electrolytebased lithium-ion cells. Three decades of research and development into solvent-free polyether-based electrolytes has seen many advances, but their commercial exploitation is still limited to operational temperatures above 40 oC. The development and commercialization of both gel-based, and solvent-free, polymer electrolytes is presented.